Clean drinking water as a sustainable development goal: Fair, universal access with increasing block tariffs - Christian von Hirschhausen; Maya Flekstad; Georg Meran (DIW Economic Bulletin, 2017)
One focus of the G20 Summit in Hamburg in July 2017 was the United Nations' sustainable development goals, including those set for the water sector. Despite progress, around 800 million people worldwide do not have adequate access to drinking water. Increasing block tariffs are an instrument widely used to support access to drinking water for poorer segments of the population. With this system, the price of water progressively increases with the volume consumed. An affordable first block ensures that poorer segments of the population have access to drinking water. However, neoclassical economic theory deems this form of tariff inefficient and advises against its use. From a behavioral economics perspective, however, it does have some advantages, which the present study discusses. In addition to their relative ease of implementation, increasing block tariffs are in line with the general public's concept of fairness: poorer population segments should pay less for vital goods.
Keywords: L51; L95; H21; D40; 330; water; tariffs; social preferences; neoclassic economics; sustainable development